Empowering EFL Students’ Reading Proficiency via the Mediated Instruction of Text (MIT) Approach - Zaky Sumarsono (Sumber Belajar Sejahtera, 2025)
This study investigated the effectiveness of the Mediated Instruction of Text (MIT) strategy in teaching reading comprehension to tenth-grade English as a Foreign Language (EFL) learners. Employing a pre-experimental one-group pre-test–post-test design, the research involved 36 students who received MIT-based instruction during a structured intervention. Reading comprehension was assessed using a multiple-choice test administered before and after the intervention. Data analysis, conducted using a paired samples t-test in SPSS 17, revealed a significant improvement in students’ reading performance. The mean pre-test score was 10.08, while the post-test mean increased to 14.94, indicating a notable gain. The t-test results, t(35) = 8.63, p < 0.05, confirmed the statistical significance of the difference, leading to the rejection of the null hypothesis. These findings demonstrate that the MIT strategy is an effective pedagogical approach to enhancing EFL learners’ reading comprehension. The study supports the incorporation of mediated strategies in EFL reading instruction to foster deeper engagement with texts and improved comprehension outcomes.